Prosodic Competence as the Missing Component of Reading Processes Across Languages: Theory, Evidence and Future Research. (4th March 2022) - Wade-Woolley, Lesly; Wood, Clare; Chan, Jessica; Weidman, Sarah
ABSTRACT: Referring to the "vital parts" of speech that do not appear in print, E. B. Huey (1908/1968) described prosody in reading as "the rise and fall of pitch and inflection, the hurrying here and slowing there, what we have called the melody of speech." In this paper, we discuss the role prosody plays in reading, contextualized in the Reading Systems Framework, as a source of linguistic knowledge that impacts the orthographic system, the lexicon, and comprehension processes in tonal and non-tonal languages. Prosody at the word, phrase, and discourse levels is considered. We also review empirical evidence from experimental, longitudinal, and training studies to show the current state of knowledge about the role of prosodic competence in reading development. We conclude the paper with recommendations for future directions in research.